Chemotherapy for hepatocellular carcinoma: current status and future perspectives - Ikeda, Masafumi; Morizane, Chigusa; Ueno, Makoto; Okusaka, Takuji; Ishii, Hiroshi; Furuse, Junji (Japanese journal of clinical oncology, 2018)
The present status and future perspectives of chemotherapy, including first-line and second-line systemic chemotherapy and hepatic arterial infusion chemotherapy were reviewed for patients with advanced hepatocellular carcinoma. Abstract Chemotherapy is one of the most important treatment modalities for advanced hepatocellular carcinoma (HCC). On the basis of the results of two pivotal Phase III placebo-controlled studies, sorafenib is currently acknowledged worldwide as the standard therapeutic agent for advanced HCC. Following the introduction of sorafenib for the treatment of HCC, Phase III trials of numerous other agents as first-line or second-line chemotherapy have been conducted to determine if any of these agents might offer superior survival benefit to sorafenib. In 2016, a clear survival benefit of regorafenib over placebo was demonstrated in HCC patients showing disease progression after sorafenib treatment. A year later, in 2017, lenvatinib has been shown to be non-inferior to sorafenib, in terms of the overall survival, in chemo-naïve patients with advanced HCC. More recently, promising outcomes have also been reported with new agents, such as nivolumab and cabozantinib. At present, various novel combination regimens including these agents are currently under development. Hepatic arterial infusion chemotherapy (HAIC) is frequently adopted for the treatment of locally advanced HCC in Japan, based on reports of high response rates and favorable long-term outcomes. Although some randomized controlled trials of HAIC plus sorafenib vs. sorafenib alone as first-line therapy have been conducted in patients with advanced HCC, no firm evidence of the superiority of one over the other has been established yet. In the future, demonstration of the survival advantage of HAIC and the recognition of HAIC as one of the standard treatments for patients with advanced HCC are expected.